HSM pocketing tool path evaluation proposition of performance criteria. (30th May 2007) - Pateloup, Vincent; Chanal, Helene; Duc, Emmanuel; Ray, Pascal
This paper presents an analysis of the performance evaluation of tool paths within the framework of high speed pocket machining. Firstly, an analysis of the needs and problems arising from pocket machining is presented and quantifiable performance criteria are defined. Secondly, applications of this performance evaluation to various test cases are presented. This performance evaluation enables a computed tool path to be evaluated before the machining operation is performed, in order to predict its feasibility and cost.